Aspirin and the Prevention of Experimental Arterial Thrombosis: Difficulty in Establishing Unequivocal Effectiveness - Reyers, Ine; Hennissen, Adje; Donati, Maria Benedetta; Hornstra, Gerard; de Gaetano, Giovanni (Thrombosis and Haemostasis, 1985)
A trial of the efficacy of aspirin in the prevention of thrombotic occlusion of an “aortic loop” in rats was made simultaneously by two experimental surgeons. A relatively large dose of aspirin (80-100 mg/kg/day) was used, starting two days before operation. It appeared that aspirin was of limited benefit, reducing thrombotic occlusions by about 17% seven days after the insertion of the loop into the abdominal aorta. Although the average occlusion time was prolonged by about 17% in aspirin-treated animals, the separate trials gave no conclusive result. When the data from both operators were pooled, a statistically significant protection by aspirin was apparent (p = 0.02), by a two-tailed Student’s t test. However, on using the powerful non-parametric randomization test, the occlusion times in control and aspirin-treated groups appeared not statistically different (p = 0.07). No significant difference was also found between control and treated groups when data were analyzed by X2 test. Independently of the statistical analysis, these data are quite similar to those obtained from aspirin trials in men surviving myocardial infarction. This finding points to the usefulness of the aorta loop as an animal model for arterial thrombosis.
Keywords: Aspirin; Clinical trials; Statistics; Experimental thrombosis